1998
DOI: 10.1002/(sici)1099-1026(1998070)13:4<235::aid-ffj733>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant properties of some commercial essential oils

Abstract: The essential oil composition of Cananga odorata, Boswellia thurifera, Cymbopogon citratus, Marjorana hortensis, Ocimum basilicum, Rosmarinus ocinalis, Cinnamomum zeylanicum and Citrus limon was analysed by GC and GC±MS, and their antimicrobial and antioxidant activity tested. Twenty-®ve dierent genera of bacteria and one fungal species were used in this study as test organisms. These included animal and plant pathogens, food poisoning and spoilage bacteria and the spoilage fungus Aspergillus niger. The volati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
147
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(153 citation statements)
references
References 5 publications
(9 reference statements)
3
147
0
3
Order By: Relevance
“…This would provide more information about the antioxidant potential of both the essential oil and extract. Phenolic groups play an important role in antioxidant activity, 59,60 hence, the presence of phenolic compounds such as carvacrol and thymol in the essential oil and carvacrol, thymol and 4-tert-butylcatechol in the extract are responsible for the antioxidant activity. It has been reported that most natural antioxidant compounds often work synergistically with each other to produce a broad spectrum of antioxidative activities that creates an effective defence system against free radical attack.…”
Section: Radical Scavenging Activity and Reducing Powermentioning
confidence: 97%
“…This would provide more information about the antioxidant potential of both the essential oil and extract. Phenolic groups play an important role in antioxidant activity, 59,60 hence, the presence of phenolic compounds such as carvacrol and thymol in the essential oil and carvacrol, thymol and 4-tert-butylcatechol in the extract are responsible for the antioxidant activity. It has been reported that most natural antioxidant compounds often work synergistically with each other to produce a broad spectrum of antioxidative activities that creates an effective defence system against free radical attack.…”
Section: Radical Scavenging Activity and Reducing Powermentioning
confidence: 97%
“…[11][12][13][14] With regard frankincense essential oils, there are many studies about chemical composition 9,15-23 and not so much about antimicrobial activities. 24,25 In this paper we report the chemical composition results determined by GC/MS analysis of essential oils from four Boswellia species oleogum resins: B. serrata, B. carteri, B. papyrifera and B. rivae and their antibacterial and antifungal activities. The aim of this study was to identify chemotaxonomy marker components of these oils and the biological results reported should encourage the medical use of these oils as antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the inhibitory activity against bacteria, yeasts, and molds of essential oils from subtropical citrus using different antifungal assays performed under various conditions (Baratta et al 1998;Belletti et al 2004;Chaisawadi et al 2003;Chathaphon et al 2008;Sharma and Tripathi 2008). Sharma and Tripathi (2008) demonstrated that C. sinensis (L.) essential oil inhibited A. niger mycelial growth (92-100% radial growth inhibition) at the concentration of 2.5-3.0 μg/ml in solid media.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the increase of consumer's demand for safe and natural preservatives, natural fungicides have been intensively investigated. Among natural antimicrobials, plant essential oils have exhibited potential inhibition against both bacteria and fungi (Baratta et al 1998;Caccioni et al 1998;Lanciotti et al 2004;Mahmud et al 2009;Melendez and Capriles 2006;Samy 2005;Soliman and Badeaa 2002;Wannissorn et al 2005). Recently, the potential antimicrobial uses of citrus essential oils were extensively reviewed (Fisher and Phillips 2008).…”
Section: Introductionmentioning
confidence: 99%